(untitled) (Res Medica, 2014)
It’s now well over a year since the cystic fibrosis gene was cloned and there is still much to be done before its localisation can be translated into an improvement in health care for affected people. I’m not going to go into any details on how the gene was located, for this information (which is rather technical) see ref. 1. However to put it rather bluntly, despite the fact that the gene has been localised and sequenced has been sequenced, no-one really knows what it does. The cystic fibrosis gene has been named the CFTR gene (cystic fibrosis transmembrane conductance regulator). It is located on the long arm of chromosome 7 and is composed of 27 extrons which code for 1,400 amino-acid residues. There seem to be several different final products of the CFTR gene which result from the removal of exons from the first nucleotide binding fold. The functional significance of these products is not known.